Augmentation of bacterial homeostasis by regulating in situ buffer capacity: Significance of total dissolved salts over acidogenic metabolism. (February 2017) - Venkata Mohan, S.; Srikanth, S.; Nikhil, G.N.
Highlights: Undissociated volatile fatty acids affects the bacterial homeostasis. Measure of buffering capacity interprets the rate of acidogenic metabolism. Bicarbonate salts can substantial influence over biohydrogen production. Abstract: During anaerobic fermentation, consequent accumulation of acidic fermented products leads to the failure of pH homeostasis. The present study aimed to comprehend the changes in buffering capacity with addition of sodium salts of hydroxide, bicarbonate and phosphate. The results showed notable augmentation in buffer capacity and cumulative hydrogen production (CHP) compared to control. The influential factor is the amount of undissociated volatile fatty acids released that affected the cell metabolism and consequently biohydrogen generation. It is inferred that among the tested salts, sodium bicarbonate has substantial buffering capacity ( β, 0.035± mol) ensuing maximum CHP (468± mL). Besides, bioelectrochemical analysis revealed variations in redox currents that aligned with biohydrogen production. The study provides valuable information on the role of inorganic dissolved salts that would be required to regulate H2 generation and acidogenesis in the aspects of acid–gas phase system.